The Role of Social Support and Coping Skills in Promoting Self-Regulated Learning Among Urban Youth. Issue 4 (May 2018) - Perry, Justin C.; Fisher, Alexandra L.; Caemmerer, Jacqueline M.; Keith, Timothy Z.; Poklar, Ashley E.
Self-regulation is a well-known construct in educational and psychological research, as it is often related to academic success and well-being. Drawing from criticisms of a lack of context applied to the investigation of this construct, the current study examined the multi-dimensional role of social support (teachers, parents, peers) and coping skills as predictors of self-regulated learning among a diverse sample of urban youth ( N = 229). Based on a cross-sectional and longitudinal design, structural equation modeling was used to test two models. Social support predicted self-regulated learning at Time 1 and Time 2 after controlling for grades. Results further indicated that coping skills did not predict self-regulated learning in either model. The implications for practice, limitations of the study, and future directions for research are discussed.